STUDENT AND CULTURE: STORY OF BANYUWANGI - Muttafaqur Rohmah (Universitas Negeri Surabaya, 2019)
Culture in the eyes of students different with adult thinking. They blinded by new cultures that suddenly appear on the surface, breaking the line of thought, releasing one by one the indigenous veins and regions that have actually become one in their souls. When they have to talk about culture, they look for things from Google, don't ask grandfather, or people who understand and are elder in their villages, because Google has a more interesting answer than they would ask the œancestors